Genetic diversity of Brazilian Brahman cattle by pedigree analysis - Cavani, Ligia [UNESP]; Silva, Rafael Medeiros de Oliveira [UNESP]; Carreño, Luis Orlando Duitama [UNESP]; Ono, Rafael Keith [UNESP]; Bertipaglia, Tássia Souza [UNESP]; Farah, Michel Marques [UNESP]; Millen, Danilo Domingues [UNESP]; da Fonseca, Ricardo [UNESP] (FapUNIFESP (SciELO), 2018)
The objective of this work was to evaluate the genetic diversity of Brahman cattle in Brazil with pedigree analysis. Genealogical records of a subpopulation were used considering all pedigree information (Pt) and the pedigree information divided into two periods (P1, from 1994 to 2004; and P2, from 2005 to 2012) or according to the raising system (Ppt, animals on pasture; or Pst, on stable). Estimates were obtained for average inbreeding coefficients, generation intervals (GI), number of equivalent known generation (CGE), number of founders (Nf), effective number of founders (fe), effective number of ancestors (fa), and founder genome equivalents (fg). The average inbreeding coefficients were 11.97, 7.79, 11.95, 11.74, and 11.31% for Pt, P1, P2, Ppt, and Pst, respectively. Average GI was 4.4 years, whereas CGE was 3.18. The fe values were similar to those of fa, which were greater than those of fg. The fe/fa and fg/fe ratios were close to 1, which indicates no genetic bottleneck and small losses by genetic drift. The genetic diversity in the Brazilian population of Brahman breed is not significantly reduced.
Keywords: Beef cattle; Founders; Genetic bottleneck; Inbreeding